2013
DOI: 10.1242/dev.088203
|View full text |Cite
|
Sign up to set email alerts
|

Ephrin B1 maintains apical adhesion of neural progenitors

Abstract: SUMMARYApical neural progenitors are polarized cells for which the apical membrane is the site of cell-cell and cell-extracellular matrix adhesion events that are essential for maintaining the integrity of the developing neuroepithelium. Apical adhesion is important for several aspects of the nervous system development, including morphogenesis and neurogenesis, yet the mechanisms underlying its regulation remain poorly understood. Here, we show that ephrin B1, a cell surface protein that engages in cell signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 43 publications
1
67
0
Order By: Relevance
“…These observations suggest that TBC1D24 regulates radial neuronal migration by maintaining ARF6 in the inactive GDP-bound state. In fact, a recent report showed that low ARF6-GTP levels are also necessary in the early stages of corticogenesis to maintain the apical localization of integrin β1 receptor in neuronal progenitors, a process crucial for apical adhesion and, therefore, for neuroepithelium integrity (15). Furthermore, the combination of TBC1D24 knockdown and overexpression of the constitutively active form of ARF6 displayed no synergistic effect on neuronal migration, leading us to hypothesize that TBC1D24 may act upstream to ARF6 pathway to control the turnover of adhesion molecules and/or the remodeling of the cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations suggest that TBC1D24 regulates radial neuronal migration by maintaining ARF6 in the inactive GDP-bound state. In fact, a recent report showed that low ARF6-GTP levels are also necessary in the early stages of corticogenesis to maintain the apical localization of integrin β1 receptor in neuronal progenitors, a process crucial for apical adhesion and, therefore, for neuroepithelium integrity (15). Furthermore, the combination of TBC1D24 knockdown and overexpression of the constitutively active form of ARF6 displayed no synergistic effect on neuronal migration, leading us to hypothesize that TBC1D24 may act upstream to ARF6 pathway to control the turnover of adhesion molecules and/or the remodeling of the cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…The TBC1D24 protein is expressed in the brain and interacts with the ADP ribosylation factor (ARF) 6, a small GTP-binding protein implicated in membrane exchange between the plasma membrane and the endocytic compartments (8,12). In the brain, ARF6 is known to play various roles including regulation of neurite outgrowth (13,14) and maintenance of apical adhesion of neural progenitors in the developing neocortex (15). Interestingly, pathogenic mutations in TBC1D24 affect its binding to ARF6 and result in a severe impairment of neuronal development (7,8,10).…”
Section: Rna Interferencementioning
confidence: 99%
“…Thus, it is possible that PlexinA1 could be acting as an integrin coreceptor required for laminin binding and attachment to the ECM. Interestingly, ephrin B1 signaling has been shown to enhance ECM adhesion of neuroepithelial cells by promoting apical localization of integrin β1 (Arvanitis et al, 2013). By analogy, loss of PlexinA1 function might impair the apical distribution of integrins in progenitor cells and, thereby, affect their ability to attach properly to the ECM and consequently impair their capacity to divide.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of the intracellular domains of Ephs regulates the recruitment of effector proteins, such as the noncatalytic regions of Tyr kinase adaptor protein 1 (Nck1) and Nck2, Vav2 and Vav3, Src, a2-chimerin, and ephexins, which directly regulate actin or modulate the activity of the small GTPases RhoA and Rac1 (Kania and Klein 2016). Normal morphogenesis of the neural tube and neural progenitors requires ephrin-dependent cellcell adhesion (Arvanitis et al 2013), and alternative usage of different splice forms of Eph receptor was implicated in mediating cell-cell coupling during embryonic development. Eph signaling promotes the formation of AJ through interaction with E-cadherin and TJs via the interaction with claudin (Dravis and Henkemeyer 2011).…”
Section: Cell-cell Adhesion Systemsmentioning
confidence: 99%